A study on the macroeconomics variables that effect bond yields in Malaysian bond market / Muhammad Zaidy Yazid - Yazid, Muhammad Zaidy (Faculty of Business and Management, 2010)
This study applies a conventional multifactor market model to emerging market bond index rates of return that are denominated in U.S. dollars. We take into account common global factors and country-specific factors, including macroeconomic factors, variables related to local bond market development, as well as political and financial risks, and consider the structural break associated with the capital flows. There are many research have been conduct in order to investigate the factors that influencing yield spreads between the developed and emerging countries namely Malaysia regarding on the Bonds Market such as (Fischer 1981, Brandt and Wang 2003),(Longstaff and Schwartz, 1995; Jarrow et al, and Collin-Dufresene et al. (2002)), Jones (1998). The knowledge has been expended by Norliza Ahmad, Joriah Muhammad and TajulAriffinMasron (2009)by exploring the influence of macroeconomic variables such as the interest rate changes, expected inflation rate, imposing of tax and effects of global crisis that can put effects on liquidity on bond issuance in Malaysia bond market. Malaysian bond market is developing rapidly but not much is understood in terms of macroeconomic factors that could influence the yield spread of the Ringgit Malaysian denominated bonds. Based on a multifactor model, this paper examines the impact of four macroeconomic factors namely: Kuala Lumpur Composite Index (KLCI), Industry Production Index (IPI), Consumer Price Index (CPI) and interest rates (IR) on bond yield spread of the Malaysian Government Securities (MGS) and Corporate Bonds (CBs) for a period from January 2001 to December 2009.